“Support the shit out of them:” intersex emerging adults’ socialization experiences and recommendations for caregivers of an intersex child - Astle, Shelby (Kansas State University, 2023)
Caregivers can play a key role in helping intersex children face a world in which intersex issues are often misunderstood, pathologized, and stigmatized. However, there is a dearth of literature centering intersex individuals’ perspectives, experiences, and needs. In order to aid caregivers in becoming more positive socialization influences for their intersex children, we aimed to (a) highlight commonly shared socialization experiences of intersex individuals across childhood and adolescence and (b) provide recommendations for caregivers of an intersex child based on these experiences. Guided by critical intersex studies (Holmes, 2009) and social cognitive theory (Bandura, 1986), I conducted interviews with 28 emerging adults (ages 18-29) who identified as intersex and/or have a variation in sex characteristics. Using thematic analysis to analyze these interviews, the coding team identified six themes of key socialization experiences that contributed to these intersex emerging adults’ meaning-making around having an intersex variation growing up: (a) We Don’t Talk About This, (b) We’re All In The Dark, (c) We Could Use Some Help, (d) I Should Be Less Me, (e) My Body Isn’t Mine, and (f) I Feel Supported and Empowered. Based on these experiences, the sample of intersex emerging adults provided recommendations for caregivers of an intersex child, which the coding team summarized in four themes: (a) Make it Okay to Talk About, (b) Get Informed and Connected. (c) Center Your Child’s Choices and Feelings, and (d) Disrupt Systems of Oppression. These findings suggest that sources of influence in the lives of intersex children and adolescents, especially caregivers, work to break the silence around intersex topics, seek education about intersex issues, connect to resources, center the child’s feelings and choices, and disrupt systems of oppression that harm intersex individuals.
Keywords: Intersex; Parenting; Thematic analysis; Emerging adults; Social cognitive theory; Queer theory